The clinical significance of mitochondrial calcium uniporter in gastric cancer patients and its preliminary exploration of the impact on mitochondrial function and metabolism - Xu, Zipeng; Chen, Xia; Zhou, Haicun; Sun, Luming; Bai, Ruobing; Yu, Wenwen; Yang, Junhao; Liu, Hongbin (Frontiers in Oncology, 2024)
The objective of this study is to elucidate the influence of MCU on the clinical pathological features of GC patients, to investigate the function and mechanism of the mitochondrial calcium uptake transporter MCU in the initiation and progression of GC, and to explore its impact on the metabolic pathways and biosynthesis of mitochondria. The ultimate goal is to identify novel targets and strategies for the clinical management of GC patients.Methods: Tumor and adjacent tissue specimens were obtained from 205 patients with gastric cancer, and immunohistochemical tests were performed to assess the expression of MCU and its correlation with clinical pathological characteristics and prognosis. Data from TCGA, GTEx and GEO databases were retrieved for gastric cancer patients, and bioinformatics analysis was utilized to investigate the association between MCU expression and clinical pathological features. Furthermore, we conducted an in-depth analysis of the role of MCU in GC patients. We investigated the correlation between MCU expression in GC and its impact on mitochondrial function, metabolism, biosynthesis, and immune cells. Additionally, we studied the proteins or molecules that interact with MCU Results: Our research revealed high expression of MCU in the GC tissues. This high expression was associated with poorer T and N staging, and indicated a worse disease-free survival period. MCU expression was positively correlated with mitochondrial function, mitochondrial metabolism, nucleotide, amino acid, and fatty acid synthesis metabolism, and negatively correlated with nicotinate and nicotinamide metabolism.Furthermore, the MCU also regulates the function of the mitochondrial oxidative respiratory chain. The MCU influences the immune cells of GC patients and regulates ROS generation, cell proliferation, apoptosis, and resistance to platinum-based drugs in gastric cancer cells.High expression of MCU in GC indicates poorer clinical outcomes. The expression of the MCU are affected through impacts the function of mitochondria, energy metabolism, and cellular biosynthesis in gastric cancer cells, thereby influencing the growth and metastasis of gastric cancer cells. Therefore, the mitochondrial changes regulated by MCU could be a new focus for research and treatment of GC.